An assessment of the external technology acquisition process of San Miguel Beer Division's (SMBD) Brewing Operations - Yumang, Ariel N. (University of the Philippines Diliman, Technology Management Center, 2006)
The project involves the assessment of the approaches of SMBD in acquiring new technologies it implements inits beer brewing process. The assessment will be based on frameworks and process models used by people in authority on the subject. It subsequently identifies the strong and weak points of the system being assessed which eventually leads to some useful recommendations for improvement and development prospects. The objectives of the project are : 1. To assess the external technology acquisition process of the San Miguel Beer Division while benchmarking against identified best practices by experts in the field. 2. To formulate recommendations for further improvement of the current external technology acquisition process. The assessment activity conducted made use of Allen Eskellin's Technology Acquisition model as its primary basis of standard. With other benchmark systems and best practices from literatures, a comprehensive model of how a successful technology acquisition process is carried out, will be formulated via a checklist of tools and tasks in each and every step of the process. The assessment process identified several good practices in the system. Among them : Comprehensiveness in how the target technology is conceptualized and presented to approving authorities. Succinctly presented justifications for the technology acquisition projects. Wide range of technical information source for technology acquisition. Vendor evaluation is systematically carried-out, is data-based, and is objectively performed. The power of special arrangements such as "Demo to Sell", "Sale or Return", "No Cure, No Pay", and "Lease to Own" Several weaknesses of the current system are as follows : Possible risks from all aspects or fronts are not extensively tackled or challenged during the initiation phase. Technical requirements do not undergo prioritization process. The document equivalent to a "Request for Proposal" does not necessarily follow a certain format. Tools and techniques used to evaluate vendor performance as far as the technical requirements are concerned are limited to simple statistics. Events, actions and procedures changes, customization, and retro-fitting activities during the implementation phase are seldom recorded or documented. Recommendations related to the weaknesses identified include the following: Potential risks engaged in the process of implementing an externally acquired technology to pass through potential problem analysis or Failure Mode and Effects Analysis (FMEA). The different technical requirements identified and established during the planning stage of the acquisition process should be analyzed for their importance to the successful implementation and operation of a project. The division has to update its evaluation tool with the use of modern tools and techniques developed by the expert in the subject - QFD, TRIZ, PDPC, FEA, etc. There is a great value to keep track of all the events, activities, and dealings with the vendor during the implementation phase of the technology acquisition project. This is particularly of utmost importance when customization, tailor-fitting, adjustments and other changes are made in the plan and/or contract.